What to expect when you're expecting (Workman Publishing, 2016)
With What to Expect’s trademark warmth, empathy, and humor, it answers every conceivable question expecting parents could have, including dozens of new ones based on the ever-changing pregnancy and birthing practices and choices they face. Advice for dads is fully integrated throughout the book. All medical coverage is completely updated, including the latest on Zika virus, prenatal screening, and the safety of medications during pregnancy, as well as a brand-new section on postpartum birth control.